Pengaruh Model Problem Based Learning Berbasis Etnomatematika Terhadap Kemampuan Pemecahan Masalah Siswa SMP - Choriah Tumanggor, Nurul; Samin Lubis, Mara; Afri, Lisa Dwi; Maysarah, Siti (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2026)
This study was motivated by students’ low problem-solving ability, which is associated with teacher-centered instruction and the limited integration of cultural contexts in mathematics learning. The purpose of this study was to examine the effect of an ethnomathematics-based Problem-Based Learning (PBL) model on students’ problem-solving ability. This research was conducted at SMP Swasta Bakti Medan in the 2024/2025 academic year, on the topic of Similarity. This research employed a quantitative approach using a nonequivalent control group design. The population comprised all of grade VII students at SMP Swasta Bakti, the sample were class VII-A as the control group and class VII-B as the experimental group, each comprising 17 students. The sampling technique used was saturated sampling (total sampling). Data were collected through essay-type tests and analyzed using a t-test. The results showed that the average improvement in problem-solving ability in the experimental group was 0.594 (moderate category), while the control group showed an average improvement of 0.274 (low category). The hypothesis testing showed that the Sig. (2-tailed) value of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. These findings demonstrate that the ethnomathematics-based PBL model has a significant effect on the problem-solving ability of grade VII students at SMP Swasta Bakti.